Ultrasound-Assisted Solvent-Free Parallel Synthesis of 3-Arylcoumarins Using N-Acylbenzotriazoles - Sirawit Wet-Osot (2018)
© 2016 American Chemical Society. An ultrasound-assisted one-pot acylation/cyclization reaction between N-acylbenzotriazoles and 2-hydroxybenzaldehydes has been developed for the synthesis of substituted 3-arylcoumarins. Using ultrasound not only allows rapid and clean conversion but also simplifies experimental setup and parallel workup leading to rapid generation of 3-arylcoumarin libraries under mild, solvent-free, and chromatography-free conditions.